Targeting complement-mediated immunoregulation for cancer immunotherapy. (June 2018) - Kolev, Martin; Markiewski, Maciej M.
Abstract: Complement was initially discovered as an assembly of plasma proteins "complementing" the cytolytic activity of antibodies. However, our current knowledge places this complex system of several plasma proteins, receptors, and regulators in the center of innate immunity as a bridge between the initial innate responses and adaptive immune reactions. Consequently, complement appears to be pivotal for elimination of pathogens, not only as an early response defense, but by directing the subsequent adaptive immune response. The discovery of functional intracellular complement and its roles in cellular metabolism opened novel avenues for research and potential therapeutic implications. The recent studies demonstrating immunoregulatory functions of complement in the tumor microenvironment and the premetastatic niche shifted the paradigm on our understanding of functions of the complement system in regulating immunity. Several complement proteins, through their interaction with cells in the tumor microenvironment and in metastasis-targeted organs, contribute to modulating tumor growth, antitumor immunity, angiogenesis, and therefore, the overall progression of malignancy and, perhaps, responsiveness of cancer to different therapies. Here, we focus on recent progress in our understanding of immunostimulatory vs. immunoregulatory functions of complement and potential applications of these findings to the design of novel therapies for cancer patients.